In the shadow of Moscow: the Stalinist reconstruction of the capitals of the Soviet republics - Čepaitienė, Rasa (Journal of Architecture and Urbanism, 2015)
Looking through the prism of USSR national policy the article analyzes the reconstruction of Stalinist cities. The study is based on the visual analysis of the city landscapes of the capitals of 12 of 15 former Soviet republics. Focusing attention on the mechanisms and tools of the formation of the capitals of the Soviet republics, the strategies and tactics of the reconstructions carried out in these cities are discussed. As their result in the late period of Stalinist culture the creation of an ideological-visual narrative of a major Soviet city, consisting of a united “content of socialist realism” and local “national forms”, was completed. The conclusion is made is that mainly using plant and geometric ornaments of local folk art in the decor of the buildings of the socialist realism style, these capitals were “marked” in a specific way. However, although this aesthetic program allowed one to distinguish visibly these cities from one another, and to highlight some of the features of national cultures, however, the fostering of such narrowly understood and apolitical “folk character” at the same time restricted the possibilities of the Soviet connected nations to keep the abilities to preserve free and uncontrolled authentic expression of their cultures.